Nanomaterials for electrochemical biosensing applications and fundamental studies - Loo, Adeline Hui Ling (2017)
Nanomaterials represent the key building blocks of nanotechnology. Due to the extensive research performed on them, a wide array of nanomaterials in different sizes, shapes and compositions are now available. In this thesis, we focus on three classes of nanomaterials, specifically graphene and its analogues, transition metal dichalcogenides, and carbon quantum dots. Attributable to their attractive physical and chemical properties, these nanomaterials are ideal candidates for signal generation and transduction in biosensing applications. Nonetheless, despite of the numerous studies conducted in an attempt to employ these nanomaterials for biosensors development, some areas remain unexplored. In particular, there is still inadequate understanding of the fundamental working principles of biosensors, and potential novel biosensing systems which are yet to be designed. In view of these, the three classes of nanomaterials in study were exploited to gain deeper insights on the fundamental principles and to explore novel biosensing systems. Specifically, graphene and its analogues were utilized to attain better understandings on the effects of DNA immobilization methods on its subsequent hybridization efficiency, and to validate the mechanism behind physical adsorption of DNA. After which, a total of four novel biosensing applications were demonstrated with graphene oxide and chemical vapour deposition fabricated graphene. With transition metal dichalcogenides, the inherent charge transfer resistance of these nanomaterials was first characterized before using them to investigate their interactions with DNA. Thereafter, the influence of different transition metals, in these nanomaterials, on their performance as a fluorescence quencher for DNA detection was studied. Finally, a new approach of using molybdenum disulfide for DNA detection was established. Last of all, for the case of carbon quantum dots, the pioneering work of adopting them as the fluorescence quencher for DNA detection was illustrated.